Clinical, cytogenetic, and molecular analysis of three families with FRAXE. Issue 1 (January 1997) - Barnicoat, A J; Wang, Q; Turk, J; Green, E; Mathew, C G; Flynn, G; Buckle, V; Hirst, M; Davies, K; Bobrow, M
Abstract : The probe StB12.3 has been used to screen the FMR-1 gene in 42 pedigrees with a distal Xq fragile site for expansion of the CCG repeat and aberrant methylation of the FRAXA locus. Four families did not have a FRAXA mutation and were investigated further. Fluorescent in situ hybridisation (FISH) and molecular analyses showed that three of these families had an expansion at FRAXE and one at FRAXE. Detailed psychiatric, psychological, and behavioural features of three families with FRAXE identified in the study are presented. All the males who expressed FRAXE had a large methylated CCG repeat at FRAXF. All males with the mutation had some degree of mental handicap. This study illustrates the need for the FRAXE phenotype to be defined further.